Ischemic Changes in the Mucous Membrane of the Transverse Colon as a Complication of Acute Pancreatitis - D. A. Semenov; S. G. Shapovalyants; D. E. Seleznev; O. I. Yudin; S. V. Korolev; N. A. Gracheva; L. M. Mikhaleva; K. S. Paramonenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to present a clinical case of a patient with a complicated course of acute pancreatitis.Key points. A 31-year-old patient was admitted to the surgical department with a clinical picture of acute alcoholic pancreatitis. Signs of anemia were regarded as a consequence of gastrointestinal bleeding. Computed tomography with contrast enhancement, along with an increase in the size of the pancreas, the presence of foci of pancreatic necrosis with multiple fluid accumulations in the parapancreatic space, revealed smoothed gaustration and thickening of the walls of the predominantly transverse colon. During colonoscopy, ischemic changes of the colon mucosa were detected in a timely manner. Negative results of analysis for toxins A and B of Clostridioides difficile and pathogenic intestinal flora were obtained. By the means of intensive care, it was possible to achieve complete stabilization of the patient's condition, normalization of laboratory blood parameters and relief of ischemic processes in the colon wall.Conclusion. Ischemic changes of the colon can serve as a complication of acute pancreatitis. A thorough analysis of the results of computed tomography at the first signs of colon lesion and colonoscopy contributed to the rapid detection of complications and prevention of irreversible colon ischemia.